Aging haloes: implications of the magnitude gap on conditional statistics of stellar and gas properties of massive haloes. Issue 1 (31st January 2020) - Farahi, Arya; Ho, Matthew; Trac, Hy
ABSTRACT: Cold dark matter model predicts that the large-scale structure grows hierarchically. Small dark matter haloes form first. Then, they grow gradually via continuous merger and accretion. These haloes host the majority of baryonic matter in the Universe in the form of hot gas and cold stellar phase. Determining how baryons are partitioned into these phases requires detailed modelling of galaxy formation and their assembly history. It is speculated that formation time of the same mass haloes might be correlated with their baryonic content. To evaluate this hypothesis, we employ haloes of mass above $10^{14}\, M_{\odot }$ realized by TNG300 solution of the IllustrisTNG project. Formation time is not directly observable. Hence, we rely on the magnitude gap between the brightest and the fourth brightest halo galaxy member, which is shown that traces formation time of the host halo. We compute the conditional statistics of the stellar and gas content of haloes conditioned on their total mass and magnitude gap. We find a strong correlation between magnitude gap and gas mass, BCG stellar mass, and satellite galaxies stellar mass, but not the total stellar mass of halo. Conditioning on the magnitude gap can reduce the scatter about halo property–halo mass relation and has a significant impact on the conditional covariance. Reduction in the scatter can be as significant as 30 per cent, which implies more accurate halo mass prediction. Incorporating the magnitude gap has a potential to improve cosmological constraints using halo abundance and allows us to gain insight into the baryon evolution within these systems.